IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA (Suatu Studi Di Badan Penanggulangan Bencana Daerah Kabupaten Minahasa Tenggara) - Londok, Christo Imanuel (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT: This research questioned the two main problems, namely: the extent to which successful implementation of disaster management policies, and Is successful implementation of disaster management policies in Southeast Minahasa district also determined or influenced by factors of communication, resources, implementing dispositions or attitudes and bureaucratic structures. Thereby, this study aims to: (1) to describe the successful implementation of disaster management in Southeast Minahasa district, (2) to determine whether the successful implementation of disaster management policies in Southeast Minahasa district also determined or influenced by factors of communication, resources, disposition or implementing attitude and bureaucratic structures.This research uses a quantitative approach to the application of descriptive and explanatory methods. The data and information collected through questionnaires distributed technique to 60 respondents, and is equipped with observation and documentation techniques, and then analyzed by applying a multiple linear regression analysis techniques.Based on the analysis of data, it is known that: (1). The success rate of implementation of disaster management in Southeast Minahasa district are in the category of "moderate/midle" or quite successful. This fact shows that the implementation of policies combating disaster in this area is not optimal . It is constrained by inadequate availability of resources, particularly the amount and quality of human resources involved in disaster management policy itself. (2). Together or simultaneous communication factors, resources, dispositions or attitudes and bureaucratic structures implementing disaster management policies significantly influence the success implemntasi disaster, but partial, there are two factors that low influence, namely: communication factors and bureaucratic structures, where the influence of both these factors were not significant.Thereby, it can be concluded that the factor of communication and bureaucratic structures should get priority attention for future improvements to optimize performance / success of the implementation of disaster management policies, particularly in Southeast Minahasa regency.Key words : policy implementation, disaster prevention